(untitled) (Journal of International Crisis and Risk Communication Research, 2021)
Glyphosate is the world’s most used and controversially debated herbicide. Its approval in the European Union (EU) is expiring in 2022. At the time of its last approval procedures in the EU in 2016/2017, there was a heated public debate in Germany about the carcinogenic risk of glyphosate. In this context, the Munich Environmental Institute published a study which concluded there were chemical residues of glyphosate in the 14 most-popular German beers. In this article, I analyze the “Gift im Bier” (poison in beer) case by examining central stakeholders’ reactions using a message-centered approach for risk communication and reflect on culturally-rooted messages, including the use of humor, within risk communication. Ultimately, I will argue for a contextsensitive and message-centered approach to risk communication analysis.